Análise faunística de Scolytidae (Coleoptera) coletadas com armadilhas etanólicas com e sem porta-isca em Eucalyptus spp. e área de cerrado no município de Cuiabá-MT - Gusmão, Rejane Soares (2011)
The objective of this study was to identify the Scolytidae diversity associated with Eucalyptus spp. and cerrado vegetation in Cuiabá, Mato Grosso state, Brazil, using ethanolic traps with and without attractive bait. This research was conducted in June 2009 – May 2010, in stands of Eucalyptus camaldulensis, urocam (Eucalyptus camaldulensis x Eucalyptus urophylla), urograndis (Eucalyptus grandis x Eucalyptus urophylla) and cerrado fragment near the plantations. Were used 32 ethanolic traps escolitídeo-Curitiba model with adaptations, eight in each stand, four using attractive bait, consisting of domestic ethanol 96 °GL, and the remaining four traps without bait attractive. In all the traps was used ethanol 70 °GL in containers collectors. Samples were collected fortnightly and the specimens were identified at the Laboratory of Forest Protection, Universidade Federal do Paraná. Were collected in traps with and without bait, respectively, 2,246 (51.7%) and 2,100 (48.3%) individuals, distributed in 21 species. Ethanol 96 °GL had no significant effect as attractive in the collection of bark beetles in the four stands. In cerrado fragment was collected largest number of individuals (34.2%), and this stand was the most diverse (H ': 2.08), while urocam had the lowest diversity (H': 1.76) and showed a lower number of individuals among populations (16.2%). In Eucalyptus stands, the population peaks occurred in the dry months, while in the cerrado the most abundant species showed population peaks during the rainy season. In the classification of communities, the cerrado fragment showed high dissimilarity in relation to eucalypts stands. The analysis employed showed the importance of species Hypothenemus eruditus, Hypothenemus obscurus, Premnobius cavipennis, Xyleborus ferrugineus, Xyleborus spinulosus and gender Cryptocarenus in planted and native forests in the region studied.